2022
DOI: 10.3389/fpls.2022.909527
|View full text |Cite
|
Sign up to set email alerts
|

Adaptative Mechanisms of Halophytic Eutrema salsugineum Encountering Saline Environment

Abstract: Salt cress (Eutrema salsugineum), an Arabidopsis-related halophyte, can naturally adapt to various harsh climates and soil conditions; thus, it is considered a desirable model plant for deciphering mechanisms of salt and other abiotic stresses. Accumulating evidence has revealed that compared with Arabidopsis, salt cress possesses stomata that close more tightly and more succulent leaves during extreme salt stress, a noticeably higher level of proline, inositols, sugars, and organic acids, as well as stress-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 161 publications
0
3
0
Order By: Relevance
“…It is well established that water is the most abundant and crucial substance within plants, but under saline-alkaline conditions, the plants are often subjected to drought and pH stress ( Otlewska et al, 2020 ). Research has revealed that a number of plants in saline-alkaline areas have evolved complex mechanisms at the physiological and molecular level to adapt to high saline-alkaline soils and drought stress ( Li et al, 2022 ). One crucial biochemical factor related to plant water content is aquaporins, and increasing evidence from various crop plants suggests that aquaporins play a vital role in drought stress tolerance ( Forrest & Bhave, 2007 ; Xu, Bruce, & Spivey, 2014 ; Zargar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that water is the most abundant and crucial substance within plants, but under saline-alkaline conditions, the plants are often subjected to drought and pH stress ( Otlewska et al, 2020 ). Research has revealed that a number of plants in saline-alkaline areas have evolved complex mechanisms at the physiological and molecular level to adapt to high saline-alkaline soils and drought stress ( Li et al, 2022 ). One crucial biochemical factor related to plant water content is aquaporins, and increasing evidence from various crop plants suggests that aquaporins play a vital role in drought stress tolerance ( Forrest & Bhave, 2007 ; Xu, Bruce, & Spivey, 2014 ; Zargar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of methionine and the deregulation of ethylene biosynthetic genes after salt stress (Table 1 and Figure 8D) suggest that ethylene synthesis is related to the methionine cycle. In addition, the higher level of stress-related proline and organic acids has been observed in salt cress (Eutrema salsugineum) exposed to extreme salt stress (Li et al, 2022). In the roots of D. officinale, proline biosynthetic genes were induced by salt and their expression was correlated with the increase in proline content.…”
Section: Discussionmentioning
confidence: 99%
“…These plants, continuously challenged by co-occurring environmental stresses, represent promising candidates for a deeper understanding of plant defense mechanisms to mixed stresses(Ozgur et al 2013;Hamed et al 2013;Ozfidan-Konakci et al 2016;Zandalinas et al 2021;Barros et al 2021;Alam et al 2022;Li et al 2022). …”
mentioning
confidence: 99%